IDENTIFIKASI DAN PENYUSUNAN STRATEGI BAGI PENGEMBANGAN EKONOMI KREATIF DALAM PENINGKATAN PEREKONOMIAN DAERAH DI BEBERAPA KABUPATEN DI PROVINSI RIAU - Fahrial, Fahrial (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
The purpose of this study is to identify and formulate strategies for the development of creative economy in improving the regional economy in several districts in Riau Province. The object of research is creative industry spread in small and medium business group (MSME) spread in each research area, that is 30.000 UMKM. The contribution of fishery sector in Indragiri Hilir Regency is analyzed through shift share analysis. The results of the analysis show that there is an increase in the contribution generated, this is due to improvements in resource management in Indragiri Hilir Regency. Assessment of economic base of Indragiri Hilir Regency in this study was calculated using Location Quotient (LQ) analysis. Based on location analysis of Location Quotient, fishery sub sector is base sector for last 5 years. The base sector according to Sjafrizal (2008) is a sector whose activities can generate revenue from outside the region, the sector whose demand function is exogenous and can increase the economic growth of the region and become the backbone of the regional economy because it has a high competitive advantage. Of the sixteen attributes on the aspect of goofness and policy focus, the average of the results of the analysis suggests a poor and a mean score. This score implies that the conditions of regional economic development and creative industries business institutions in Indragiri Hilir Regency are viewed from the aspect of going and low policy focus. So this condition also demands better management through a series of integrated policies. The scores were then analyzed using the Rafed technique. The value of sustainability index of regional economic development and fishery business institution of Indragiri Hilir Regency on the aspect of go-go and the policy focus obtained by Rafed technique is 52,34. Based on the sustainability criteria, the sustainability status on the aspect of going on and the focus of this policy is on a fairly sustainable status. The stress value obtained on the Aspect of Going Out and Policy Focus is 0.1392 (13.92 percent) or still below 25 percent so Rafed's analysis meets the condition of good of fit. The value of R2 obtained is 95.27 percent, which means the model using the current variables has explained 95.27 percent of the existing model. The result of leverage analysis for the aspect of go-go and the policy focus on regional economic development and creative industry business institution of Indragiri Hilir Regency that there is no dominant attribute influence the sustainability of regional economic development and creative industry business institution of Indragiri Hilir Regency from Aspect of Going and Policy Focus, the highest leverage factor values are Community Development Policy, Interregional / Local Government Cooperation Policy and Business Competition Policy